2016
DOI: 10.1371/journal.pone.0157573
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias for Reward and Punishment in Overweight and Obesity: The TRAILS Study

Abstract: More than 80% of obese adolescents will become obese adults, and it is therefore important to enhance insight into characteristics that underlie the development and maintenance of overweight and obesity at a young age. The current study is the first to focus on attentional biases towards rewarding and punishing cues as potentially important factors. Participants were young adolescents (N = 607) who were followed from the age of 13 until the age of 19, and completed a motivational game indexing the attentional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…Attentional bias to general cues of reward and punishment. The Spatial Orientation Task (SOT [24]), an adaptive reaction time task, was used to measure attention towards cues of general reward and punishment [25,34]. See the Supporting information for a detailed description of the task,.…”
Section: Methodsmentioning
confidence: 99%
“…Attentional bias to general cues of reward and punishment. The Spatial Orientation Task (SOT [24]), an adaptive reaction time task, was used to measure attention towards cues of general reward and punishment [25,34]. See the Supporting information for a detailed description of the task,.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were run on 96.24% of the data. Consistent with a series of recent studies using RT-based performance measures (e.g., [ 50 , 51 , 52 ]), we decided to use median instead of mean reaction times because this seems the most simple, straightforward, and robust way to deal with outliers without losing too much information. Median scores were computed for the different presentation times and type of trials (valid/invalid), for all stimulus types.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is currently controversially debated whether this model developed in the context of addiction applies also to obesity ( 6 , 19 , 20 , 27 31 ). Previous studies have shown an abnormal sensitivity to rewards and reward-predicting cues in obese individuals ( 32 38 ) but did not test whether this modulates goal-directed behavior. Here, we address this question and investigate whether food-predicting cues differentially influence goal-directed behavior of normal-weight, overweight, and obese individuals.…”
Section: Introductionmentioning
confidence: 91%